The Effectiveness of the Si Kemad Information System in Improving Public Services at DPMPTSP Dharmasraya - Reza Sepriani; Kelik Purwanto; Alex Ferdinal (Goodwood Publishing, 2026)
Purpose: This study aims to analyze the effectiveness of the Community Satisfaction Information System (Si Kemad) in enhancing public services at the Office of Investment and One-Stop Integrated Services (DPMPTSP) in the Dharmasraya Regency. Research Methodology: This study employed a descriptive qualitative approach and was conducted at the DPMPTSP Dharmasraya. Data were collected through semi-structured interviews, direct observations, and document analysis. The informants included agency leaders, system operators, frontline staff, and service users. The Si Kemad function serves as a digital survey system based on Google Forms and is periodically evaluated. Results: The results indicate that Si Kemad is moderately effective in improving community participation, expediting service delivery, and supporting data-driven decision-making. However, challenges remain, particularly in areas such as public socialization, human resource limitations, and underdeveloped technological infrastructure. Conclusions: The Si Kemad program has contributed to improving the quality of public services. However, further optimization and stronger technical and institutional support are necessary to maximize its potential. Limitations: This study was limited to a single institutional setting and applied a qualitative approach; thus, the findings may not be generalizable to broader contexts. Contributions: This study contributes to the advancement of digital-based public service models, particularly in regional government settings. These findings offer insights for practitioners, scholars, and policymakers in public administration and government information systems.